2003
DOI: 10.1097/01.asn.0000097862.14805.06
|View full text |Cite
|
Sign up to set email alerts
|

Regression Lines in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) has been recognized for millennia. The great physicians Rhazes (865-925 AD) and Abu Sina (aka Avicenna, 980 -1037 AD) in ancient Persia described kidney diseases in detail. In medieval times, the pisse prophets predicted outcomes for patients on the basis of uroscopy analyses. Categorization of CKD developed in the 20 th century from the nonspecific "Bright's disease" with the advent of renal biopsy analysis. Patients could now survive with CKD with dialysis, made possible by the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
(12 reference statements)
1
15
0
Order By: Relevance
“…Angiotensin II stimulates ECM protein synthesis directly v i a both hemodynamic and nonhemodynamic mechanisms and induces fibrogenic molecules such as TGF-β 1 and MCP-1, while inhibiting matrix degradation by directly inducing PAI-1 and TIMP-1 [127,128]. Growing evidence suggests significant fibrogenic actions of aldosterone [129].…”
Section: Prevention and Regression Of Renal Fibrosismentioning
confidence: 99%
“…Angiotensin II stimulates ECM protein synthesis directly v i a both hemodynamic and nonhemodynamic mechanisms and induces fibrogenic molecules such as TGF-β 1 and MCP-1, while inhibiting matrix degradation by directly inducing PAI-1 and TIMP-1 [127,128]. Growing evidence suggests significant fibrogenic actions of aldosterone [129].…”
Section: Prevention and Regression Of Renal Fibrosismentioning
confidence: 99%
“…Blocking these common mechanisms and modulation of fibrotic agents may inhibit the progression of CKD, independent of the underlying primary disease. Synergistic therapies could halt the progression of fibrosis and may potentially cause regression of any existing renal scarring [3,8,9] .…”
mentioning
confidence: 99%
“…A study in type 1 diabetic patients with nephropathy showed that after isolated pancreas transplantation, partial reversal of glomerular pathology had occured after 10 years [84], implying the possibility of glomerular self repair. Partial reversal of glomerulosclerosis has also been observed in nondiabetic models of renal damage after administration of high doses of ACEIs or angiotensin receptor blockers [3,4,85]. Whether in the future this will be a realistic therapeutic goal in humans as well is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%